The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15241/mg.6.2.147
|View full text |Cite
|
Sign up to set email alerts
|

The Process and Implications of Diagnosing Oppositional Defiant Disorder in African American Males

Abstract: This study surveyed male counselor educators regarding the impact of being male upon their professional relationships. Participants (N=163) were surveyed about their attitudes concerning the influence of gender on their relational behavior, as well as their relationship practices with students and colleagues. Mixedmethods analyses revealed a majority of respondents believed being male influenced their relationship behavior and reported experiencing relationship challenges unique to male counselor educators. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Similar patterns occur among mental health professionals. When white patients and Black patients present identical symptoms, Black patients are less likely to receive treatment for depression (Simpson et al 2007) and more likely to be diagnosed with psychotic and childhood disorders (Schwartz and Feisthamel 2009), schizophrenia (Blow et al 2004;Barnes 2013; see also Neighbors et al 2003), and oppositional and conduct disorders (Baglivio et al 2016;Grimmett et al 2016). In the criminal justice context, psychological risk assessments have been the subject of a great deal of scrutiny, and several studies have found that in a wide variety of contexts, these assessmentswhich range a great deal in terms of how purely actuarial or algorithmic they areadvantage white defendants and parole candidates and disadvantage Black defendants and parole candidates (for example, Angwin and Larson 2016;Isard 2017;but cf.…”
Section: ) Psychologists' Assessments Of Mental Health and Dangerousnessmentioning
confidence: 99%
“…Similar patterns occur among mental health professionals. When white patients and Black patients present identical symptoms, Black patients are less likely to receive treatment for depression (Simpson et al 2007) and more likely to be diagnosed with psychotic and childhood disorders (Schwartz and Feisthamel 2009), schizophrenia (Blow et al 2004;Barnes 2013; see also Neighbors et al 2003), and oppositional and conduct disorders (Baglivio et al 2016;Grimmett et al 2016). In the criminal justice context, psychological risk assessments have been the subject of a great deal of scrutiny, and several studies have found that in a wide variety of contexts, these assessmentswhich range a great deal in terms of how purely actuarial or algorithmic they areadvantage white defendants and parole candidates and disadvantage Black defendants and parole candidates (for example, Angwin and Larson 2016;Isard 2017;but cf.…”
Section: ) Psychologists' Assessments Of Mental Health and Dangerousnessmentioning
confidence: 99%
“…Among noted differential diagnoses is oppositional defiant disorder (ODD), which is marked by defiant behaviors, arguing, fighting with peers and adults, easy annoyance, and disrespect for authority. Sadly, research overwhelming reports overdiagnosis of Black males with ODD (Arredondo, 1999; Cossu et al, 2015; Grimmett et al, 2016; Ratts et al, 2015). Students who are struggling academically may, in fact, learn to avoid displaying their vulnerabilities by engaging in these negative compensatory behaviors.…”
Section: Dyslexia and The Misdiagnosis Of Black Malesmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T 5 AA families often receive poor quality mental health services, frequently drop out of care, and experience discrimination in their interactions with child serving systems (Alegria et al, 2015;Copeland, 2006;Grimmett et al, 2016;Office of Surgeon General, 2001;McKay & Bannon Jr, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…13 accompany primary caregivers to group meetings as these individuals are critically important to families in the AA communities (Copeland, 2006;Grimmett et al, 2016). We presumed that the inclusion of kin/fictive kin could lessen the caregivers' feelings of isolation as well as provide instrumental and emotional support.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation